Terrestrial-aquatic transfers by hippopotamus (Hippopotamus amphibius): effects on food web and benthic community structure of the St Lucia Estuary, iSimangaliso Wetland Park, World Heritage Site, South Africa - Dawson, Jessica (Department of Biological Sciences, 2020)
Africa’s last extant aquatic megaherbivore, the hippopotamus, facilitates linkages between terrestrial and aquatic systems at scales, frequencies and intensities that are probably unmatched by any other natural process. Through defaecation of terrestrial grasses into aquatic habitats, hippos disproportionately enhance boundary permeability across the aquaticterrestrial divide. Little, however, is known about the ecological ramifications of these transfers for recipient communities and broader functioning in aquatic ecosystems, with equivalent knowledge for estuaries being virtually non-existent. Using a combination of in situ (1) experiments manipulating hippo dung inputs, (2) assessments of carbon and nitrogen stable isotope ratios and (3) fatty acid analyses, I aimed to quantify the influence of hippo dung on food web and benthic community structure in the St Lucia Estuary - a subtropical estuarine lake on the east coast of South Africa. It was hypothesized that experimental dung enrichment at high levels would result in significant declines in benthic community metrics and that food web components in biotopes with contrasting hippo numbers would differ in isotopic and fatty acid signatures. Results from experiments revealed that effects of hippo dung on benthic assemblages were assemblage specific. Microphytobenthic biomass was reduced by up to 70 %; macrobenthic abundance, biomass and richness declined by 76, 56 and 27 % respectively, while meiofauna were negligibly impacted by experimental dung enrichment. Results therefore suggest a greater resilience of meiofauna to high dung inputs relative to microphytobenthos and macrofauna. Comparisons of food web components from biotopes with contrasting hippo numbers (the Narrows: hippos dense; Charter’s Creek: hippos rare) indicated distinct consumer isotopic and fatty acid profiles, suggesting different dietary sources. Contrary to expectations, stable isotope mixing models revealed a greater reliance on hippo dung as a food source by consumers in Charter’s Creek (i.e. where hippos were rare). Fatty acid biomarkers suggested that in the presence of heavy dung loading, consumer diets incorporated VI less benthic diatoms, more bacteria, and generally reflected stronger dependence on terrestrial food sources. Overall, this study demonstrates the potential for hippo dung to influence consumers and trophic interactions due to its role as a trophic resource and modifier of abiotic conditions. However, findings of in situ experiments also show that in high amounts, dung inputs can lead to declines in benthic metrics. Apart from enhancing understanding of the broader roles hippos play in aquatic ecosystems, this study highlights considerations relevant to managing hippo populations and dung inputs, especially under drought conditions. This is central to maintenance of ecological functioning in a system that is regarded as a biodiversity hotspot and key tourist attraction. Specifically, it is important that water levels are managed to prevent dung accumulation and deleterious effects, particularly on the benthos.